Nitrogen, Phosphorus, and Potassium Fertilization for Newly Established Tall Fescue - D. W. Sweeney; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2015)
First-year spring yields of tall fescue in 2013 responded to phosphorus (P) fertilization, but lodging at the R5 growth stage in the spring with higher P fertilization rates may have influenced subsequent fall harvest yields, which declined with increasing P rates. As N rates increased, R5 yields declined but fall harvest yields increased.
Keywords: tall fescue; cool-season grass; fertilizer